(untitled) (Journal of Business and Management Research, 2020)
This study examined effects of business process reengineering (BRP) on organisational performance in the food and beverage industry in Nigeria. The study adopted survey research design and multistage sampling methods. It utilised primary data generated thorugh a questionnaire for the research. Multiple regression analysis was employed to analyse the data. On the hypothesis one, the findings showed that organisational resources and process function have negative and insignificant effect on competitive advantage but innovative thinking has a positive and significant effect on competitive advantage. On the hypothesis two, all the components of business process reengineering (organizational resources, innovative thinking and process function) have positive and significant effect on operational performance. Thus, the study concluded when organizational resources, innovative thinking and process function are combined together as business process reengineering components, they enhance organizational performance in the food and beverages industry in Nigeria. The study suggested that Food and Beverages firms should continue to formulate policies that will encourage innovative ideas from all stakeholders of the organizations in order to continue to achieve competitive advantage and experience sound operational performance. The process function of the organization should continue to be designed and redesigned so that they enjoy smooth operational performance, obtain new resources and upgrade the existing ones so that the firms could achieve competitive advantage. The process function and organization resources need to be evaluated and appraised from time to time to know or detect any lapses that may hinder the firms from attaining their short and long term business goals.